Preparation and optimization of aloe ferox gel loaded with Finasteride-Oregano oil nanocubosomes for treatment of alopecia - Khaled M. Hosny; Waleed Y. Rizg; Eman Alfayez; Samar S. Elgebaly; Abdulmohsin J. Alamoudi; Raed I. Felimban; Hossam H. Tayeb; Rayan Y. Mushtaq; Awaji Y. Safhi; Majed Alharbi; Alshaimaa M. Almehmady (Taylor & Francis Group, 2022)
Alopecia areata is a skin disorder characterized by scarless, localized hair loss that is usually managed by topical treatments that might further worsen the condition. Therefore, the current study aimed to develop nano-cubosomes loaded with finasteride (FI) and oregano oil (Or) to improve drug solubility and permeation through skin and then incorporate it into an aloe ferox gel base. An l-optimal coordinate exchange design was adopted to optimize nano-cubosomes. Phytantriol and Alkyl Acrylate were employed as the lipid material, and surfactant respectively for cubosomes manufacture. The produced formulations were assessed for their particle size, entrapment efficiency (EE%), FI steady-state flux (Jss) and minimum inhibitory concentration (MIC) against Pro-pionibacterium acnes. Optimal FI-Or-NCu had a particle size of 135 nm, EE% equals 70%, Jss of 1.85 μg/cm2.h, and MIC of 0.44 μg/ml. The optimum formulation loaded gel gained the highest drug release percent and ex vivo skin permeation compared to FI aqueous suspension, and pure FI loaded gel. Aloe ferox and oregano oil in the optimized gel formulation had a synergistic activity on the FI permeation across the skin and against the growth of p. acne bacteria which could favor their use in treating alopecia. Thus, this investigation affirms the ability of FI-Or-NCu loaded aloe ferox gel could be an effective strategy that would enhance FI release and permeation through skin and maximize its favorable effects in treating alopecia.